Elymus (Poaceae) as a model for climate-resilient crop design - Yu, Shuguang; Dorji, Tsechoe (Frontiers in Plant Science, 2026)
The escalating climate crisis demands that agriculture move beyond the incremental improvement of domesticated crops. We posit that the wild perennial grass genus Elymus offers a novel and powerful model for this transition. By synthesizing recent genomic, ecological, and physiological evidence, we show that the evolutionary success of these complex polyploids rests on three interconnected foundational principles: a dynamic “negotiated” allopolyploid genome balancing structural innovation with meiotic stability; a modular toolkit of molecular, microbial, and epigenetic components orchestrating stress resilience; and keystone ecosystem engineering functions enhancing soil health and carbon sequestration. Decoding this integrated “Elymus Model” provides a transformative framework that shifts the paradigm from transferring isolated traits to the principled design of crops and agroecosystems whose inherent multi-scale architecture confers productivity, sustainability, and climate resilience.